Word smart II : how to build a more educated vocabulary - Robinson, Adam; Princeton Review (Firm) (New York : Villard Books, 1993)
More than eight hundred additional words to help build an impressive vocabulary compiled by the staff of The Princeton Review will help anyone communicate more effectively and enhance the ability to take standardized tests.
Keywords: Vocabulary; English language; SAT (Educational test) -- Study guides